Gentlemen of uncertain fortune : how younger sons made their way in Jane Austen's England - Muir, Rory, 1962- (Yale University Press, 2019)
A portrait of Jane Austen's England told through the career paths of younger sons-men of good family but small fortune. In Regency England the eldest son usually inherited almost everything while his younger brothers, left with little inheritance, had to make a crucial decision: what should they do to make an independent living? Rory Muir weaves together the stories of many obscure and well-known young men, shedding light on an overlooked aspect of Regency society. This is the first scholarly yet accessible exploration of the lifestyle and prospects of these younger sons.